(untitled) (International Journal of Management and Sustainability, 2018)
Fast changing digital technologies are disrupting and changing business, product life cycles are becoming shorter and putting pressure on companies to bring a new product to market quick still cheaper and better this new technological wave warrant companies to put product innovation and development at the forefront. Data has become vital for business leaders across every industry; they are looking for a digital model to increase the efficiency and effectiveness of product lifecycle. These new trends in digital technology are shaping future of product lifecycle, Big data, Internet of things, cognitive and text analytics has come forward to the new edge of digital enabled innovation over the past few years. Big data analytics has become vital for business leaders across every industry sector. While many companies have used it to extract new insights and create new forms of value, other companies have yet to leverage big data to extend the life cycle of their products.